2016
DOI: 10.1093/toxsci/kfw121
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Subvisible Aggregates of Immunogenic Proteins Promote a Th1-Type Response

Abstract: Protein aggregation is associated with enhanced immunogenicity of biotherapeutics. As a result, regulatory guidelines recommend screening for aggregation during bioprocessing. However, the mechanisms underlying the enhanced immunogenicity of aggregates are poorly understood. In the investigations described herein, the immunogenicity in mice of a humanized single chain variable antibody fragment (scFv) purified after expression in Escherichia coli has been examined. Reproducible scFv aggregates were obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…Additionally, aggregation alone significantly enhanced the anti‐scFv IgM response (*** P < 0·001). This effect of aggregation on IgM antibody levels has previously been reported 22. The addition of DnaK enhanced the IgG2a anti‐scFv response in aggregated preparations (** P < 0·01), but was without effect on IgG1 or IgM antibody production.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Additionally, aggregation alone significantly enhanced the anti‐scFv IgM response (*** P < 0·001). This effect of aggregation on IgM antibody levels has previously been reported 22. The addition of DnaK enhanced the IgG2a anti‐scFv response in aggregated preparations (** P < 0·01), but was without effect on IgG1 or IgM antibody production.…”
Section: Resultssupporting
confidence: 83%
“…This was expected as we have previously shown that subvisible‐sized aggregates of scFv promote a Th1‐skewed response 22. It is possible that the Th1 skewing is an effect of differential antigen processing and presentation, and this effect is also consistent with the hypothesis that the repetitive epitopes formed by aggregation can mimic characteristics of microbes and viruses 28.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations